Conductometric Equilibrium Study of Methylmethionine Sulfonium Chloride - Vora, J.J.; Bhutadiya, L.S. (Asian Journal of Chemistry, 2010)
In this study, the determination of dissociation constant of methyl-methionine sulfonium chloride (MMSC) by conductance measurements at different concentrations had been carried out. The measurements were carried out at 25 ± 0.1 ºC and 35 ± 0.1 ºC. Equivalent conductance, degree of dissociation, K, pK and dissociation constants are also calculated.